2012
DOI: 10.1007/s13105-012-0170-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of leucine on energy balance

Abstract: Body weight is determined by the balance between energy intake and energy expenditure. When energy intake exceeds energy expenditure, the surplus energy is stored as fat in the adipose tissue, which causes its expansion and may even lead to the development of obesity. Thus, there is a growing interest to develop dietary interventions that could reduce the current obesity epidemic. In this regard, data from a number of in vivo and in vitro studies suggest that the branched-chain amino acid leucine influences en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 73 publications
0
20
0
Order By: Relevance
“…A longer duration of WPI intake (21 weeks) was found to significantly increase the adipose tissue expression of β-3AR compared with that of the control HFD group ( 57 ) . These data suggest the possibility that WPI increases lipolysis in adipocytes via the activation of β-3AR, possibly arising as a consequence of the effects of dietary protein on the central nervous system, given that central nervous system outflow to the adipose tissue activates β-3AR ( 37 , 38 , 58 , 59 ) .…”
Section: Discussionmentioning
confidence: 86%
“…A longer duration of WPI intake (21 weeks) was found to significantly increase the adipose tissue expression of β-3AR compared with that of the control HFD group ( 57 ) . These data suggest the possibility that WPI increases lipolysis in adipocytes via the activation of β-3AR, possibly arising as a consequence of the effects of dietary protein on the central nervous system, given that central nervous system outflow to the adipose tissue activates β-3AR ( 37 , 38 , 58 , 59 ) .…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, Zhang et al [64] showed that HFD fed mice on leucine-supplemented drinking water have reduced fasting plasma levels of aspartic acid, glutamic acid, and phenylalanine, as well as increased VO 2 and reduced adiposity compared to HFD controls. Given the influence of leucine on WPI-induced muscle hypertrophy [65], [66] and its unique ability to regulate the translation of protein synthesis [67], it is possible that the elevated leucine content found normally in the WPI diets may have enhanced muscle protein synthesis by directing other amino acids towards protein synthesis and/or catabolism [68], [69], with the required energy been derived possibly from fat catabolism [70]. Consistent with the latter suggestion, we found an increased lean mass and a trend towards a reduction in fat mass with decreased plasma levels of several amino acids, but not leucine, when the casein protein in a HFD was replaced with WPI or when the P/C ratio in the HFD was increased.…”
Section: Discussionmentioning
confidence: 99%
“…The leucine sensing structures are located in the mediobasal hypothalamus (including the arcuate and ventromedial nuclei) and the dorsal vagal complex of the caudal brainstem (including the nucleus of the solitary tract, the dorsal motor vagus and the area postrema). In these brain areas, leucine induces neurons to express the anorexigenic proopiomelanocortin (POMC) that reduces feeding and body weight gain (McAllan et al, ) (Figure ).…”
Section: Branched‐chain Amino Acid Pharmacodynamicsmentioning
confidence: 99%